A case report of neoadjuvant targeted therapy in stage IIIA non-small cell lung cancer with BRAF V600E mutation - Peng, Wenying; Qu, Susu; Cai, Lijuan; Yang, Runxiang; Dong, Mengyuan; Li, Xiang; Ran, Fengming; Luo, Chunxiang (Frontiers in Medicine, 2025)
For advanced or metastatic non-small cell lung cancer (NSCLC) with actionable gene mutations, first-line targeted therapy significantly prolongs survival compared to chemotherapy and immunotherapy. Perioperative targeted therapy has achieved significant improvement in early- and locally advanced-stage NSCLC patients with epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK) mutations. However, there have been few reports of neoadjuvant treatment in patients with non-small cell lung cancer with rare mutations, such as BRAF (V-Raf murine sarcoma viral oncogene homolog B) V600E mutation. In this report, we present a case of inoperable stage IIIA lung adenocarcinoma with a BRAF V600E mutation that underwent radical lung cancer surgery following neoadjuvant targeted therapy. The postoperative pathology review revealed a pathological complete response (pCR). This case illustrates that BRAF and mitogen-activated extracellular signal-regulated kinase (MEK) inhibitor therapy may represent a viable option for neoadjuvant therapy in locally advanced BRAF V600E mutant NSCLC.